Effects of unilateral backpack carriage on biomechanics of gait in adolescents: a kinematic analysis - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2012)
Objective: The aim of this study was to analyze the biomechanical alterations during unilateral backpack carriage in adolescents and to compare the kinematic parameters of the loaded and unloaded sides. Methods: Twenty adolescents (mean age: 13 +/- 1.2 years) were assessed during walking with no backpack and with a backpack on one shoulder. The kinematic parameters of a gait at a self-selected speed were analyzed using motion analysis. Specific kinematic peak points were compared between asymmetric walking; unloaded, loaded side and mean of unloaded walking. Results: Peak ankle dorsal flexion, mean knee varum angle, peak value of hip extension and range of pelvic rotation decreased; and knee flexion at initial contact, hip adduction angle, mean pelvic anterior tilt and mean pelvic obliquity increased on the loaded side relative to the unloaded side and unloaded walking. Decreased maximum hip extension during late stance, increased hip adduction, elevated pelvis and increased anterior pelvic tilt were seen on the loaded side and the pelvis was lowered, ankle dorsal flexion increased and the hip was abducted on the unloaded side as a counter effect. Conclusion: Both the unloaded and loaded sides were affected by asymmetrical backpack carriage. The biomechanical alterations seen in asymmetrical backpack carriage may put some extra load on the lumbar vertebral joints and altered frontal knee biomechanics contribute to low back pain and pathologies in the knee joint.
Keywords: Asymmetric school bag carrying; backpack; gait analysis; kinematic analysis; loading; LOAD; CHILDREN; WALKING; PAIN; ALIGNMENT; POSTURE; BAGS